Decision Support System for Selecting Social Media Platforms for Gen Z Personal Branding Using the TOPSIS Method - Dyah Irmawati; Yulaikha Mar’atullatifah (Sah Publisher, 2026)
The development of social media has encouraged Generation Z to utilize it as a primary means of building personal branding. However, the large number of social media platforms creates difficulties in determining the most appropriate and effective platform. This study aims to determine the best social media platform to support Generation Z's personal branding using a Decision Support System (DSS) approach with the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. This study used a quantitative design with primary data obtained through questionnaires. The research respondents were Generation Z who actively use social media. The alternatives analyzed included five social media platforms evaluated based on seven assessment criteria relevant to personal branding needs. Data were analyzed using the TOPSIS method through the stages of compiling a decision matrix, normalization, weighting, determining positive and negative ideal solutions, calculating Euclidean distance, and determining preference values. The results showed that Instagram obtained the highest preference value of 0.5726 and was ranked first, followed by LinkedIn, TikTok, and YouTube. Meanwhile, alternative X (Twitter) had the lowest preference value, namely 0.2046. These findings demonstrate that the TOPSIS method is capable of providing an objective and systematic ranking of alternatives. This research contributes to providing a decision-making model that can be used as a practical reference for Generation Z in selecting optimal social media platforms for personal branding.